2017
DOI: 10.3389/fendo.2017.00253
|View full text |Cite
|
Sign up to set email alerts
|

Culture in Glucose-Depleted Medium Supplemented with Fatty Acid and 3,3′,5-Triiodo-l-Thyronine Facilitates Purification and Maturation of Human Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: With recent advances in stem cell technology, it is becoming efficient to differentiate human pluripotent stem cells (hPSCs) into cardiomyocytes, which can subsequently be used for myriad purposes, ranging from interrogating mechanisms of cardiovascular disease, developing novel cellular therapeutic approaches, as well as assessing the cardiac safety profile of compounds. However, the relative inability to acquire abundant pure and mature cardiomyocytes still hinders these applications. Recently, it was report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…All of the cardiomyocyte cultures started beating 6–8 days post induction of differentiation. On days 20–27, a subset of cultures was treated with T3 (methods), which was shown to aid in the maturation of iPSC-derived cardiomyocytes 20 , 24 , 26 . We assessed the purity of the iPSC-derived cardiomyocytes using flow cytometry (Methods) for cardiac troponin I (TNNI3) and cardiac troponin T (TNNT2).…”
Section: Resultsmentioning
confidence: 99%
“…All of the cardiomyocyte cultures started beating 6–8 days post induction of differentiation. On days 20–27, a subset of cultures was treated with T3 (methods), which was shown to aid in the maturation of iPSC-derived cardiomyocytes 20 , 24 , 26 . We assessed the purity of the iPSC-derived cardiomyocytes using flow cytometry (Methods) for cardiac troponin I (TNNI3) and cardiac troponin T (TNNT2).…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether ETV1 has a conserved function in human HPS specification, we investigated whether ectopic ETV1 induction in hiPSC-CMs would convert these cells toward a HPS lineage. Using a protocol previously validated for the generation of purified and mature hiPSC-CMs 71 , we infected hiPSC-CM monolayers with Ad-Etv1-EGFP or Ad-EGFP. Two weeks post-transduction, cells were collected for either RNA or cellular electrophysiological analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NCRM1 iPSC line from Codex BioSolutions Inc. (MD, USA) were plated on Geltrex LDEV-Free Reduced Growth Factor Basement Membrane Matrix (Gibco, A1413202) coated plates and cultured with Essential 8 Medium (Gibco, A1517001). The differentiation and maturation protocol has been previously published 71 . Briefly, day one hiPSC were treated with small molecule CHIR99021 (Tocris, 4423, final concentration 10 μM) in the RPMI-BSA medium [RPMI 1640 Medium (HyClone, SH30027.01) supplemented with 213 μg/ml AA2P (l-ascorbic acid 2-phosphate magnesium) (A8960, Sigma) and 0.1% bovine serum albumin (BSA) (A1470, Sigma)] for 24 h followed by RPMI-BSA medium replacement.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, metabolically selected PSC-derived cardiomyocytes enhance the ratio of OCR/ECAR by 1.8-fold compared to non-purified cardiomyocytes (61) , suggesting that this method forces the metabolic maturation from embryonic to neonatal cardiomyocytes. These metabolic shifts of cardiomyocytes result into more mature action potentials and calcium handling with increased expression of cardiomyocyte-related ion channels and cardiac contraction genes (62) . Researchers reported that activated glycolysis inhibited cardiac maturation through pentose phosphate pathway, which supplies NADPH, nucleotides, and lipids for proliferation.…”
Section: Metabolism In Differentiated Mature Cardiomyocytesmentioning
confidence: 99%